2021
DOI: 10.1093/cid/ciab771
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Illness Outbreaks Reported Through the National Outbreak Reporting System—United States, 2009–2019

Abstract: Background The National Outbreak Reporting System (NORS) captures data on foodborne, waterborne, and enteric illness outbreaks in the United States. The aim of this study is to describe enteric illness outbreaks reported during 11 years of surveillance. Methods We extracted finalized reports from NORS for outbreaks occurring during 2009–2019. Outbreaks were included if they were caused by an enteric etiology or if any patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…outbreaks contributed the most deaths and hospitalizations after norovirus with a case fatality and hospitalization only second to Escherichia coli . 4 Furthermore, the major presenting symptoms in our cohort were fever and bloody diarrhea. Previously published data by NORS during 2009–2019 indicated that among 2,449 Salmonella spp.…”
Section: Discussionmentioning
confidence: 78%
“…outbreaks contributed the most deaths and hospitalizations after norovirus with a case fatality and hospitalization only second to Escherichia coli . 4 Furthermore, the major presenting symptoms in our cohort were fever and bloody diarrhea. Previously published data by NORS during 2009–2019 indicated that among 2,449 Salmonella spp.…”
Section: Discussionmentioning
confidence: 78%
“…The National Outbreak Reporting System (NORS) collects information about outbreaks transmitted by food, water, environmental sources, infected persons or animals, or unknown modes of transmission ( 23 ). State, local, and territorial public health agencies submit reports to CDC that document outbreak characteristics, food and animal sources, and the pathogens that caused each outbreak.…”
Section: Methodsmentioning
confidence: 99%
“…At this time the reporting platform was renamed the National Outbreak Reporting System (NORS) [ 25 ]. Detailed descriptive statistics of the NORS, including temporal and spatial patterns, are available in earlier publications [ 26 28 ]. The publicly available data from NORS were extracted for the period 1998–2017 [ 29 ].…”
Section: Data Descriptionmentioning
confidence: 99%